Hydrodynamic Boundary Layer Flow of Chemically Reactive Fluid over Exponentially Stretching Vertical Surface with Transverse Magnetic Field in Unsteady Porous Medium - M. Sulemana; I. Y. Seini; O. D. Makinde (Journal of Applied Mathematics)
This article addresses the hydrodynamic boundary layer flow of a chemically reactive fluid over an exponentially stretching vertical surface with transverse magnetic field in an unsteady porous medium. The flow problem is modelled as time depended dimensional partial differential equations which are transformed to dimensionless equations and solved by means of approximate analytic method. The results are illustrated graphically and numerically and compared with previously published results which shown a good agreement. Physically increasing Eckert number of a fluid amplifies the kinetic energy of the fluid, and as a novelty, the Eckert number under the influence of chemically reactive magnetic field is effective in controlling the kinematics of hydrodynamic boundary layer flow in porous medium. Interestingly, whilst the Eckert number amplifies the thermal boundary layer thickness and velocity as well as the concentration of the fluid, the presence of the magnetic field and the strength of the chemical reaction have a retarding effect on the flow. Also, the chemical reaction parameter and permeability of porous medium are effective in reducing skin friction in chemically reactive magnetic porous medium and are relevant in practice because reduced skin friction enhances the efficiency of a system. The results of the current study are useful in solar energy collector systems and materials processing.